Theorising Identities in Digital Space: Filters, Avatars and Evolving Ludic Cultures - Jorlin Jose (Digital Crossroads: Integrating Humanities, Science and Technology Edition 1, 2025)
Technological proliferation and its rapid intersections with virtual and real are transforming our understanding of the body in digital spaces. The body in digital space is no longer a mere simulation or representation of the physical body but rather a distinct form of embodiment shaped by the mediated affordances of digital technology. The continued alterations in this understanding have critical implications for the issues of identity and agency. Shaped by this context, the paper situates digital identity as a fluid and context-dependent construct, highlighting the importance of continually negotiating and renegotiating one’s identity in response to changing prospects of ‘filter culture’. The qualitative study is rooted in the vogue of avatars of Metaverse, Instagram and Snapchat filters, which equip individuals to derive a digital persona skewed out of their physicality. By examining the patterns of interaction that shape and are shaped by digital identities, the paper aims to theorise spatial performativity - how spaces are actively created, shaped, and given meaning through performative actions. The paper also traces how technocultural determinism - the notion that technological advancements shape and determine cultural practices, societal structures, and human behaviour, sets body and identity apart in terms of digital cues of self. The insights into glocalisation and the malleable nature of digital identities lead to theorising ‘exportable’, ‘replayable’ and ‘remouldable’ bodies.